2009
DOI: 10.1177/0269881109103113
|View full text |Cite
|
Sign up to set email alerts
|

Abuse liability and safety of oral lisdexamfetamine dimesylate in individuals with a history of stimulant abuse

Abstract: Lisdexamfetamine dimesylate (LDX) is the first prodrug stimulant and is indicated for the treatment of attention-deficit/hyperactivity disorder. A single-centre, double-blind, randomised, placebo-controlled, 6-period crossover study evaluated the abuse potential of single oral doses of 50, 100 (equivalent to 40 mg d-amphetamine), and 150 mg LDX, 40 mg d-amphetamine and 200 mg diethylpropion in 36 individuals with a history of stimulant abuse. On the primary abuse liability measure, maximum change of the Drug R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 12 publications
8
115
0
Order By: Relevance
“…Of the doses tested, only d-amphetamine and LDX at the highest dose (150 mg) differed significantly from placebo in craving scores on the Drug Rating Questionnaire-Subject (DRQS) scale. In a pair-wise comparison of equivalent doses, d-amphetamine (40 mg) was associated with significantly higher craving scores compared with LDX (50 or 100 mg), indicating that abuse liability ("drug craving") is attenuated with LDX 22 . There are no studies available on the abuse potential of LDX compared with other controlled-release stimulants used in the treatment of ADHD, and there are as yet no data available for populations other than adults.…”
Section: Potential For Abusementioning
confidence: 93%
See 2 more Smart Citations
“…Of the doses tested, only d-amphetamine and LDX at the highest dose (150 mg) differed significantly from placebo in craving scores on the Drug Rating Questionnaire-Subject (DRQS) scale. In a pair-wise comparison of equivalent doses, d-amphetamine (40 mg) was associated with significantly higher craving scores compared with LDX (50 or 100 mg), indicating that abuse liability ("drug craving") is attenuated with LDX 22 . There are no studies available on the abuse potential of LDX compared with other controlled-release stimulants used in the treatment of ADHD, and there are as yet no data available for populations other than adults.…”
Section: Potential For Abusementioning
confidence: 93%
“…The hydrolysis of the inactive component to the active drug is a relatively slow process that occurs mainly in the blood [19][20][21] . It has been suggested that this relatively slow stage contributes to the long-lasting effect and possibly also to reduced "drug craving", an aspect considered critical in the development of abuse after both oral and intravenous administration 19,22 .…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…79 The prodrug formulation of dextroamphetamine, lisdexamfetamine, has a lower abuse potential than other stimulants and thus may be considered. 80,81 However, physicians should be aware that any psychoactive medication can be misused. As for all patients, it is important to carefully monitor medication adherence.…”
Section: Prescribing Medications For Adhd In Context Of Active Sudmentioning
confidence: 99%
“…LDX also produces similar feelings of subjective drug-liking on questionnaires in human volunteers as the 50% lower doses of AMPH base (Jasinski and Krishnan, 2009). The higher dose need likely represents the amount needed to achieve similar peak plasma AMPH concentrations and increases in the NAc DA levels, which at an equimolar ratio emerge slower and remain lower due to its extended absorption time of LDX.…”
Section: Action Of Substituted Amphetamines and Cathinonesmentioning
confidence: 85%